2012
DOI: 10.1161/circoutcomes.112.965285
|View full text |Cite
|
Sign up to set email alerts
|

Clopidogrel Use and Hospital Quality in Medically Managed Patients With Non–ST-Segment–Elevation Myocardial Infarction

Abstract: Background— Clopidogrel prescription is a class I guideline recommendation for medically managed patients with non–ST-segment–elevation myocardial infarction (NSTEMI). However, clopidogrel has historically been underused in this population. We evaluated contemporary rates of its use and evaluated associated factors, with a particular focus on hospital quality of myocardial infarction (MI) care. Methods and Results— We examined clopidogrel prescription r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
13
1
1
Order By: Relevance
“…However, understanding that this variation in premature discontinuation exists is an important initial step to further evaluate the causes of the variation in subsequent research. This finding differs from previous studies that demonstrated associations between hospital characteristics and guideline‐recommended inplantable cardioverter‐defibrillator utilization14 and clopidogrel prescription at discharge for medically managed NSTEMI patients 9. These outcomes are largely dictated by provider behaviour, while premature clopidogrel discontinuation is influenced by both patients and providers.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…However, understanding that this variation in premature discontinuation exists is an important initial step to further evaluate the causes of the variation in subsequent research. This finding differs from previous studies that demonstrated associations between hospital characteristics and guideline‐recommended inplantable cardioverter‐defibrillator utilization14 and clopidogrel prescription at discharge for medically managed NSTEMI patients 9. These outcomes are largely dictated by provider behaviour, while premature clopidogrel discontinuation is influenced by both patients and providers.…”
Section: Discussioncontrasting
confidence: 91%
“…Variability in prescription drug spending,6 cardiac procedures such as implantable cardioverter‐defibrillator implantation,7, 8 and provider adherence to established practice guidelines9 have been demonstrated. A prior study from our group showed significant national hospital‐level variation ranging from 22% to 97% in clopidogrel use for medically managed non–ST‐segment elevation myocardial infarction (NSTEMI) patients at hospital discharge 9. It is unknown whether similar variations occur in premature clopidogrel discontinuation in an integrated health care system such as the Veterans Affairs (VA) where all patients have prescription drug coverage and where copayments are low.…”
Section: Introductionmentioning
confidence: 99%
“…5 Accordingly, current AMI guidelines since 2002 call for the use of dual antiplatelet therapy with P2Y12 inhibitors and aspirin in all patients with AMI for a minimum of 12 months, irrespective of CAD obstruction or receipt of PCI. 19 Similar gaps in P2Y12 inhibitor use in medically managed AMI patients have been seen in other populations, 20 and our current findings in the TRIUMPH registry further underscore the need for improvement.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, guidelines recommend 12 months of clopidogrel treatment for NSTEMI patients, including those who did not undergo coronary revascularization . Yet prior data have shown that only half of medically managed NSTEMI patients receive clopidogrel at discharge . Whether CURE data apply to a more contemporary NSTEMI population with higher rates of evidence‐based secondary prevention use is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…1 Yet prior data have shown that only half of medically managed NSTEMI patients receive clopidogrel at discharge. 4,5 Whether CURE data apply to a more contemporary NSTEMI population with higher rates of evidence-based secondary prevention use is unknown. Among older MI patients, the perceived increased risk of bleeding may reduce provider willingness to consider clopidogrel use.…”
mentioning
confidence: 99%